A Unique Case of Spontaneous Pneumomediastinum in a Patient With COVID-19 and Influenza Coinfection - Sathishkumar Ramalingam MD; Harkesh Arora MD; Kulothungan Gunasekaran MD; Maheswari Muruganandam MD; Sivakumar Nagaraju MD (SAGE Publishing, 2021)
Spontaneous pneumomediastinum is reported in patients with coronavirus disease-2019 (COVID-19) and influenza infection independently, usually associated with noninvasive and mechanical ventilation. We report a case of spontaneous pneumomediastinum in a patient with COVID-19 and influenza coinfection. A 58-year-old male admitted with shortness of breath, diagnosed with COVID-19 and influenza infection. A computed tomography angiogram showed pneumomediastinum. He was treated conservatively with 15 L of oxygen, remdesivir, convalescent plasma, and oseltamivir. The case is being reported for its uniqueness since this is the first documented case of spontaneous pneumomediastinum in COVID-19 and influenza coinfection.